Magnetohydrodynamic natural convection in trapezoidal cavities - Hasanuzzaman, M.; Öztop, Hakan Fehmi; Rahman, M. M.; Rahim, N. A.; Saidur, R.; Varol, Y. (Pergamon-Elsevier Science Ltd, 2012)
A computational numerical work has been done to see the effects of magnetic field on natural convection for a trapezoidal enclosure. Both inclined walls and bottom wall have constant temperature where the bottom wall temperature is higher than the inclined walls. Top wall of the cavity is adiabatic. To investigate the effects, finite element method is used to solve the governing equations for different parameters such as Rayleigh number, Hartmann number and inclination angle of inclined wall of the enclosure. It is found that heat transfer decreased by 20.70% and 16.15% as phi increases from 0 to 60 at Ra = 10(5) and 10(6) respectively. On the other hand, heat transfer decreased by 20.28% and 13.42% as Ha increases from 0 to 50 for Ra = 10(5) and 10(6) respectively. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Trapezoidal enclosure; Natural convection; Magnetic field